Pressure dependent surface morphology and Raman studies of semicrystalline poly(indole-5-carboxylic acid) by the Langmuir-Blodgett technique - Pandey R.K.; Upadhyay C.; Prakash R. (My University, 2025)
Surface morphology and crystallinity play important roles in achieving high performance devices based on polymer thin films. The Langmuir-Blodgett (LB) method has been explored for the formation of uniform and ordered poly(indole-5-carboxylic acid) (5CPIn) films. The surface pressure vs. area isotherm of 5CPIn over a water subphase gives four distinct regions indicating a gaseous phase, a liquid condensed phase, a solid condensed phase and a region of collapsing solid and the formation of bilayers. The deposited monolayers of 5CPIn over indium tin oxide (ITO) substrates at different control pressures (in the selected regions of the pressure isotherm) are used to study the morphology and crystallinity. Our study reveals the region of pressure where one can obtain uniformity (at the nano level) and continuity of the films up to a few hundreds of a micron. Additionally, a comparative study using scanning electron microscopy, UV-vis spectroscopy and Raman spectroscopy indicates that the films obtained by the LB technique are significantly different to the films obtained by electropolymerization (EP) and drop casting (DC) techniques. The LB film of 5CPIn shows a more uniform morphology, a red shift of the highest absorption peak, and better crystallinity in comparison to the EP and DC polymer films. Additionally it also shows potential for polymer thin film devices. © 2013 The Royal Society of Chemistry.